Developing E-learning Web Based Using ADDIE Model In Engineering Department For ACM - Al-Sa'di, Ahmad Abdel Kareem Mohammad (2008)
In recent years, information technology has played an important role in the business field. E-learning has gained a significant popularity and it is expected to continue in the future. E-learning is a multi-dimensional activity where each dimension should be adequately supported by an E-learning system to provide a fruitful learning experience to its users. This research introduces a (EPEN) E-Learning Process Engineering Network prototype for Asian Composites Manufacturing Sdn Bhd (ACM) by providing engineering department with the necessary information and helps them reduce and manage the time by using (ADDIE) model.